ANALISIS PELAKSANAAN SISTEM INFORMASI AKUNTANSI PENJUALAN UNTUK MENINGKATKAN PENGENDALIAN INTERN PADA PT IRON BIRD LOGISTICS SURABAYAANALISIS PELAKSANAAN SISTEM INFORMASI AKUNTANSI PENJUALAN UNTUK MENINGKATKAN PENGENDALIAN INTERN PADA PT IRON BIRD LOGIS - Diah Kurnia Sari; Sri Rahayuningsih (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This study aims to analyze how credit sales accounting information systems in an effort to improve the internal control system at PT Iron Bird Logistics'. Data collection techniques used are interviews, documentation, and observation. the steps taken to achieve the objectives of this study are identification of credit sales accounting information systems, analysis of the procedures that make up the credit sales accounting information system, analyzing the flowchart of existing credit sales accounting information systems in the company, flowchart recommendations for companies The results showed that the weakness of PT Iron Bird Logistics' credit sales system was in the credit function section, the lack of searching for information about customer credit status. In addition, the company also does not apply payment terms, there is no agreement between the seller and the buyer with a cash discount, the term of payment, and the amount of the discount given.